Quality Testing of the Tigaraksa Police Public Complaints Website Using ISO/IEC 29119 - Muhammad Sodikin; Indra Kosasih; Chairul Anwar (Takaza Innovatix Labs Ltd., 2026)
The rapid development of web-based public complaint systems in the Indonesian police sector, such as POLTRAMAN at Polsek Tigaraksa, aims to enhance accessibility, transparency, and efficiency in handling community reports amid digital transformation challenges. This study evaluates the quality of the POLTRAMAN website using ISO/IEC 29119 standards to ensure reliability and usability. Employing a quantitative descriptive approach with Software Testing Life Cycle (STLC), the research applies black box testing for functional aspects and non-functional testing (performance, accessibility, best practices, SEO) via Google Lighthouse. The population consists of 7 core modules of the website, with a purposive sample of 5 main pages tested across desktop and mobile using Chrome, Firefox, and Edge browsers. Data analysis involves descriptive metrics conversion and statistical summaries like response time averages. Results reveal 100% functional test pass rate, good overall non-functional scores (average response time 2100 ms, low error rate 0-0.20%), high accessibility and SEO, although dashboard and report creation pages require optimization for dynamic loads. In conclusion, POLTRAMAN is deemed feasible for public service, with recommendations for JavaScript lazy loading to boost mobile performance